A carbon sheet-carbon nanotube material and its preparation method and application
By growing ultrafine carbon nanotubes in situ on the surface of the carbon sheet, a three-dimensional electronic conductive network is formed, which solves the problem of insufficient performance caused by the insulation of the sulfur element of lithium-sulfur batteries, and achieves a high specific surface area and multi-dimensional conductive path, which significantly improves the battery discharge capacity and lifespan.
Patent Information
- Application Number
- CN202310116106.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-15
AI Technical Summary
Due to the insulation of the positive electrode active substance sulfur element, lithium sulfur batteries have low actual discharge capacity, poor rate performance and short cycle life. The existing carbon materials have limited conductivity dimensions, making it difficult to effectively improve battery performance.
The method of growing ultrafine carbon nanotubes in situ on the surface of carbon sheets is adopted to form a three-dimensional electronic conductive network to avoid insulator sulfur deposition hindering electron transport and increase the specific surface area of the material.
By forming multi-dimensional electronic conductive paths and high specific surface area carbon sheet-carbon nanotube materials, the discharge specific capacity of lithium-sulfur batteries is significantly improved and the cycle life of the battery is extended.
Smart Images

Figure CN115974054B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a carbon sheet-carbon nanotube material and a preparation method and application thereof. Background Art
[0002] The theoretical energy density of lithium-sulfur batteries is as high as 2600Wh / kg, which is several times that of current lithium-ion batteries. In addition, the price of sulfur, the active material of the positive electrode, is cheap, non-toxic and pollution-free. Therefore, lithium-sulfur batteries have received extensive attention from industry and academia and are considered to be excellent candidates for the next generation of energy storage systems.
[0003] However, since the sulfur element, the active material of the positive electrode, is an insulator, it neither conducts electrons nor transports lithium ions, so lithium-sulfur batteries have problems such as low actual discharge capacity, poor rate performance and short cycle life. Mixing carbon materials with good conductivity, large specific surface area and low density with sulfur to prepare a composite sulfur positive electrode is one of the most effective ways to improve the poor conductivity of the active material sulfur. At present, carbon materials such as conductive carbon nanoparticles (zero-dimensional), carbon nanotubes (one-dimensional) and graphene (two-dimensional) are widely used in sulfur positive electrodes. These materials effectively improve the discharge specific capacity and rate performance of lithium-sulfur batteries.
[0004] However, there are a large number of physical contact interfaces between low-dimensional carbon nanoparticles or carbon nanotubes, and insulating solid sulfur-based substances will be deposited at the interface during the cycle process, hindering the electron transfer between carbon particles, resulting in rapid attenuation of battery performance; although two-dimensional graphene can inhibit the impact of sulfur-based substance deposition and achieve better electrochemical performance, it is currently difficult to use in large quantities due to its high price. The dimensions of the conductive path of the carbon material synthesized in the prior art are limited, and the performance of the application in lithium-sulfur batteries is limited. For example, a method for preparing carbon nanotubes disclosed in CN 105174244 uses nitrates or acetates of three substances, Fe, Al, and Mg, as raw materials, citric acid as a complexing agent and pore-forming agent, mixed into a solution and roasted to make a catalyst, and then catalytically cracked the carbon source to obtain carbon nanotubes. It uses the traditional catalytic cracking method to prepare carbon nanotubes. There are a large number of physical contact interfaces between carbon nanotubes, which will still hinder electron transfer, and the conductive performance cannot be well exerted.
[0005] Based on the above research, it is necessary to provide a method for preparing a carbon sheet-carbon nanotube material. The preparation method is not only low in cost, but the obtained carbon sheet-carbon nanotube material has a multi-dimensional electronic conductive path and a high specific surface area, which can effectively improve the discharge specific capacity of the lithium-sulfur battery. Summary of the invention
[0006] The purpose of the present invention is to provide a carbon sheet-carbon nanotube material and a preparation method and application thereof. The preparation method relates to a method for in-situ growing ultrafine carbon nanotubes on the surface of a carbon sheet, so that the obtained carbon sheet-carbon nanotube material has a three-dimensional electronic conductive network, avoiding the problem of electron transmission being blocked due to the deposition of insulator sulfur, and the prepared carbon sheet-carbon nanotube material has a high specific surface area, and effectively improves the discharge specific capacity of a lithium-sulfur battery when used as a sulfur carrier.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a carbon sheet-carbon nanotube material, the preparation method comprising the following steps:
[0009] (1) mixing and drying a template, a carbon source and a solvent to obtain a powder;
[0010] (2) annealing the powder in step (1) and then washing it to obtain a carbon sheet;
[0011] (3) mixing a metal salt, an organic ligand, a solvent and the carbon sheet of step (2), and then performing solid-liquid separation and drying to obtain a mixture;
[0012] (4) Carbonizing the mixture of step (3) to obtain the carbon sheet-carbon nanotube material.
[0013] The preparation method of the present invention first prepares an ultrathin carbon sheet, and then grows carbon nanotubes in situ on the carbon sheet to obtain a carbon sheet-carbon nanotube material. When preparing the carbon sheet, the present invention first evenly mixes a template agent and a carbon source and then freeze-dries them to make the template agent crystallize into ultrafine and fluffy crystals, so that the carbon source can be adsorbed on the template agent, promoting the generation of thinner carbon sheets, and then annealing and washing to remove the template agent to obtain the carbon sheet; then the carbon sheet is mixed with a metal salt and an organic ligand, so that one side of the metal salt is dispersed and adsorbed on the carbon sheet and the other side is connected to the organic ligand, and then the obtained mixture is carbonized to grow on the surface of the carbon sheet to obtain ultrafine carbon nanotubes.
[0014] Preferably, the mass ratio of the template to the carbon source in step (1) is (30-50):1, for example, 30:1, 40:1 or 50:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] Since the carbon source is adsorbed on the template during the preparation of the carbon sheet, the template and the carbon source described in the present invention will affect the thickness of the carbon sheet on the one hand, and on the other hand, they will also affect the uniformity of the thickness of the carbon sheet. A suitable mass ratio of the two is conducive to the synthesis of thinner carbon sheets, and thinner carbon sheets are conducive to the subsequent growth of ultrafine carbon nanotubes.
[0016] Preferably, before freeze-drying in step (1), the mixed solution is solidified using liquid nitrogen.
[0017] Preferably, the template in step (1) comprises a chloride salt, preferably sodium chloride and / or potassium chloride.
[0018] Preferably, the carbon source in step (1) comprises any one of glucose, starch or sucrose or a combination of at least two thereof, and a typical but non-limiting combination comprises a combination of glucose and starch.
[0019] Preferably, the solvent in step (1) comprises deionized water.
[0020] Preferably, the mixing time in step (1) is 20-40 min, for example, 20 min, 30 min, 40 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] Preferably, the annealing temperature in step (2) is lower than the melting point of the template in step (1).
[0022] The synthesis principle of the carbon sheet of the present invention is not to melt-cast the template chloride salt, but to adsorb the organic carbon source on the surface of the chloride salt template by freeze-drying, and anneal at a temperature lower than the melting point of the template to carbonize the organic carbon source to generate a carbon sheet.
[0023] Preferably, the annealing temperature in step (2) is 650-760°C, for example, 650°C, 670°C, 690°C, 710°C, 730°C, 750°C or 760°C, and the time is 1-3h, for example, 1h, 2h or 3h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the cleaning solution used in step (2) comprises deionized water and alcohol.
[0025] Preferably, the cleaning in step (2) is performed 3-5 times, for example, 3 times, 4 times or 5 times.
[0026] Preferably, the mixing of the metal salt, the organic ligand, the solvent and the carbon sheet of step (2) in step (3) comprises first mixing the metal salt, the solvent and the carbon sheet of step (2), and then adding the organic ligand for mixing.
[0027] Preferably, the time for adding the organic ligand and mixing is 0.5-5 min, for example, 0.5 min, 1 min, 2 min, 3 min, 4 min or 5 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] In order to adsorb metal ions on the carbon sheet and avoid the metal salt and the organic ligand from generating a framework structure, the present invention mixes the organic ligand last, and then adds the organic ligand after the metal salt and the carbon sheet are fully mixed. The mixing time after the organic ligand is added is controlled within a short time. On the one hand, the metal ions can be adsorbed on the carbon sheet, and on the other hand, the organic ligand can grow above the metal ions, thereby avoiding the metal salt and the organic ligand from growing into a crystalline metal-organic framework compound with an octahedral structure.
[0029] Preferably, the time for mixing the metal salt, the solvent and the carbon sheet in step (2) is 20-28 hours, for example, 20 hours, 22 hours, 24 hours, 26 hours or 28 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the solid-liquid separation method in step (3) includes suction filtration.
[0031] Preferably, the drying method in step (3) includes freeze-drying.
[0032] The freeze-drying method used in step (3) of the present invention can avoid the growth of the metal organic framework on the one hand, and prevent the agglomeration of the metal particles on the other hand, so that the metal particles can be evenly dispersed on the carbon sheet, thereby making the grown carbon nanotubes evenly distributed. If high-temperature drying is used, the metal particles on the carbon sheet will agglomerate, affecting the uniformity and morphology of the carbon nanotube growth.
[0033] Preferably, the metal salt in step (3) comprises nitrate.
[0034] Preferably, the nitrate comprises cobalt nitrate and nickel nitrate.
[0035] Preferably, the organic ligand in step (3) comprises dimethylimidazole.
[0036] Preferably, the solvent in step (3) comprises an alcohol solvent, preferably methanol.
[0037] Preferably, the carbonization gas in step (4) comprises an inert gas, or a mixture of a reducing gas and an inert gas.
[0038] The present invention preferably performs carbonization in a mixed gas of reducing gas and inert gas, wherein the reducing gas can promote the growth of carbon nanotubes. If carbonization is performed in pure inert gas, the morphology of the carbon nanotubes will be affected.
[0039] Exemplarily, the volume ratio of the reducing gas to the inert gas is (3-10):(90-97), for example, 3:97, 5:95 or 10:90, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the carbonization temperature in step (4) is 900-1000°C, for example, 900°C, 950°C, or 1000°C, and the time is 1-3h, for example, 1h, 2h or 3h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, step (4) further includes cooling and washing steps after the carbonization.
[0042] Preferably, the washing comprises first washing the carbonized product 3-5 times, for example, 3 times, 4 times or 5 times, with a mixed solution of deionized water and acid, and then washing it 3-5 times, for example, 3 times, 4 times or 5 times, with a mixed solution of deionized water and alcohol.
[0043] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0044] (1) mixing the template, the carbon source and the solvent for 20-40 minutes, and then freeze-drying to obtain a powder;
[0045] The mass ratio of the template to the carbon source is (30-50):1;
[0046] (2) annealing the powder in step (1) at 650-760° C. for 1-3 h, and then washing with deionized water and alcohol for 3-5 times to obtain a carbon sheet;
[0047] (3) firstly mixing the metal salt, the solvent and the carbon sheet described in step (2) for 20-28 hours, then adding the organic ligand and mixing for 0.5-5 minutes, and then performing solid-liquid separation and freeze-drying to obtain a mixture;
[0048] (4) Carbonizing the mixture of step (3) at a temperature of 900-1000° C. for 1-3 h in a mixed gas of reducing gas and inert gas, cooling, and then washing the carbonized product 3-5 times with a mixed solution of deionized water and acid, and then washing it 3-5 times with a mixed solution of deionized water and alcohol, to obtain the carbon sheet-carbon nanotube material.
[0049] In a second aspect, the present invention provides a carbon sheet-carbon nanotube material, wherein the carbon sheet-carbon nanotube material is prepared by the preparation method described in the first aspect.
[0050] In a third aspect, the present invention provides a lithium-sulfur battery, wherein the positive electrode material of the lithium-sulfur battery comprises sulfur and the carbon sheet-carbon nanotube material described in the second aspect.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The present invention adopts low-cost raw materials to first prepare carbon sheets, and then in-situ grow carbon nanotubes on the carbon sheets. At the same time, the mutual coordination between each step is utilized to make one side of the metal salt dispersed and adsorbed on the carbon sheet, and the other side is connected with the organic ligand. After carbonization, ultrafine carbon nanotubes can be grown on the surface of the carbon sheet, so that the obtained carbon sheet-carbon nanotube material has a multi-dimensional electronic conductive path and a high specific surface area, and also has a three-dimensional electronic conductive network. When used as a sulfur carrier, the problem of sulfur deposition blocking the electron transmission of carbon materials is avoided, and the discharge specific capacity of the lithium-sulfur battery is effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a transmission electron microscope image of the carbon sheet-carbon nanotube material described in Example 1 of the present invention;
[0054] Figure 2 This is a charge and discharge curve diagram of a lithium-sulfur battery prepared using the carbon sheet-carbon nanotube material as a carrier as described in Example 1 of the present invention. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0056] Example 1
[0057] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material, the preparation method comprising the following steps:
[0058] (1) 80 g of sodium chloride, 2 g of glucose and 400 mL of deionized water were stirred and mixed for 30 min to obtain a mixed solution, and the obtained mixed solution was solidified with liquid nitrogen and freeze-dried to obtain a powder;
[0059] The mass ratio of sodium chloride to glucose is 40:1;
[0060] (2) annealing the powder in step (1) at 750° C., which is lower than the melting point of sodium chloride, for 2 h, cooling to room temperature, and washing three times with a mixed solution of deionized water and alcohol to obtain a carbon sheet;
[0061] (3) First, 0.5 mol of cobalt nitrate hexahydrate, 0.5 mol of nickel nitrate hexahydrate and 1.0 g of the carbon sheet described in step (2) were added to 200 mL of methanol, mixed and stirred for 24 h, and then dimethylimidazole was added and stirred for 1 min, followed by suction filtration and freeze-drying to obtain a mixture;
[0062] (4) carbonizing the mixture of step (3) at 950° C. for 2 h in a mixed gas of hydrogen and argon in a volume ratio of 5:95, cooling to room temperature, and then washing the carbonized product three times with a mixed solution of deionized water and hydrochloric acid, and then washing it three times with a mixed solution of deionized water and alcohol, to obtain the carbon sheet-carbon nanotube material;
[0063] The transmission electron microscope image of the carbon sheet-carbon nanotube material in this embodiment is as follows Figure 1 As shown, the charge and discharge curve of the lithium-sulfur battery prepared by combining the carbon sheet-carbon nanotube material and sulfur as the positive electrode material is as shown in Figure 2 shown.
[0064] Example 2
[0065] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material, the preparation method comprising the following steps:
[0066] (1) 60 g of potassium chloride, 2 g of glucose and 400 mL of deionized water were stirred and mixed for 20 min to obtain a mixed solution, and the obtained mixed solution was solidified with liquid nitrogen and freeze-dried to obtain a powder;
[0067] The mass ratio of potassium chloride to glucose is 30:1;
[0068] (2) annealing the powder of step (1) at 650° C., which is lower than the melting point of potassium chloride, for 3 h, cooling to room temperature, and washing the powder with a mixed solution of deionized water and alcohol for 4 times to obtain a carbon sheet;
[0069] (3) First, 0.5 mol of cobalt nitrate hexahydrate, 0.5 mol of nickel nitrate hexahydrate and 1.0 g of the carbon sheet described in step (2) were added to 200 mL of methanol, and the mixture was stirred for 28 h. Then, dimethylimidazole was added and stirred for 0.5 min. Then, the mixture was filtered and freeze-dried to obtain a mixture.
[0070] (4) In a mixed gas of hydrogen and argon in a volume ratio of 10:90, the mixture of step (3) is carbonized at a temperature of 1000° C. for 1 hour, cooled to room temperature, and then the carbonized product is washed 5 times with a mixed solution of deionized water and hydrochloric acid, and then washed 5 times with a mixed solution of deionized water and alcohol, to obtain the carbon sheet-carbon nanotube material.
[0071] Example 3
[0072] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material, the preparation method comprising the following steps:
[0073] (1) 100 g of sodium chloride, 2 g of glucose and 400 mL of deionized water were stirred and mixed for 40 min to obtain a mixed solution, and the obtained mixed solution was solidified with liquid nitrogen and freeze-dried to obtain a powder;
[0074] The mass ratio of sodium chloride to glucose is 50:1;
[0075] (2) annealing the powder in step (1) at 760° C., which is lower than the melting point of sodium chloride, for 1 h, cooling to room temperature, and then washing three times with a mixed solution of deionized water and alcohol to obtain a carbon sheet;
[0076] (3) First, 0.5 mol of cobalt nitrate hexahydrate, 0.5 mol of nickel nitrate hexahydrate and 1.0 g of the carbon sheet described in step (2) were added to 200 mL of methanol, and the mixture was stirred for 20 h. Then, dimethylimidazole was added and stirred for 5 min. Then, the mixture was filtered and freeze-dried to obtain a mixture.
[0077] (4) In a mixed gas of hydrogen and argon in a volume ratio of 3:97, the mixture of step (3) is carbonized at a temperature of 900° C. for 1 hour, cooled to room temperature, and then the carbonized product is washed 4 times with a mixed solution of deionized water and hydrochloric acid, and then washed 4 times with a mixed solution of deionized water and alcohol, to obtain the carbon sheet-carbon nanotube material.
[0078] Example 4
[0079] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that in step (1), the amount of sodium chloride is 40 g and the mass ratio of sodium chloride to glucose is 20:1.
[0080] Example 5
[0081] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that in step (1), the amount of sodium chloride is 120 g and the mass ratio of sodium chloride to glucose is 60:1.
[0082] Example 6
[0083] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that the annealing temperature in step (2) is 801° C.
[0084] Example 7
[0085] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that the annealing temperature in step (2) is 600°C.
[0086] Example 8
[0087] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1, except that the dimethylimidazole described in step (3) is added into methanol together with cobalt nitrate hexahydrate, nickel nitrate hexahydrate and the carbon sheet, and the mixture is stirred for 24 hours.
[0088] Example 9
[0089] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that dimethylimidazole is added and stirred for 10 minutes in step (3).
[0090] Example 10
[0091] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that dimethylimidazole is added and stirred for 0.1 min in step (3).
[0092] Embodiment 11
[0093] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that the freeze drying in step (3) is replaced by heating drying at 90°C.
[0094] Example 12
[0095] This embodiment provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as that of Embodiment 1 except that the carbonization in step (4) is performed in pure argon.
[0096] Comparative Example 1
[0097] This comparative example provides a method for preparing a carbon material, the preparation method comprising the following steps:
[0098] (1) adding 0.5 mol of cobalt nitrate hexahydrate, 0.5 mol of nickel nitrate hexahydrate and dimethylimidazole to 200 mL of methanol, stirring the mixture for 24 h, and then filtering and freeze-drying the mixture to obtain a mixture;
[0099] (2) carbonizing the mixture of step (1) at 950° C. for 2 h in a mixed gas of hydrogen and argon in a volume ratio of 5:95, cooling to room temperature, and then washing the carbonized product three times with a mixed solution of deionized water and hydrochloric acid, and then washing it three times with a mixed solution of deionized water and alcohol to obtain the carbon material.
[0100] Comparative Example 2
[0101] This comparative example provides a method for preparing a carbon material, the preparation method comprising the following steps:
[0102] (1) 80 g of sodium chloride, 2 g of glucose and 400 mL of deionized water were stirred and mixed for 30 min to obtain a mixed solution, and the obtained mixed solution was solidified with liquid nitrogen and freeze-dried to obtain a powder;
[0103] The mass ratio of sodium chloride to glucose is 40:1;
[0104] (2) The powder of step (1) is annealed at 750° C., which is lower than the melting point of sodium chloride, for 2 h, cooled to room temperature, and then washed three times with a mixed solution of deionized water and alcohol to obtain the carbon material.
[0105] Comparative Example 3
[0106] This comparative example provides a method for preparing a carbon sheet-carbon nanotube material. The preparation method is the same as Example 1 except that the freeze drying in step (1) is replaced by heating drying at 90°C.
[0107] The carbon sheet-carbon nanotube material obtained in the above embodiment and the carbon material obtained in the comparative example were respectively mixed with sulfur element at a mass ratio of 15:85, and then treated in a vacuum oven at 155° C. for 12 h to obtain a sulfur positive electrode powder. The obtained sulfur positive electrode powder, conductive carbon (Super P), carbon nanotubes and polyvinylidene fluoride (PVDF) were mixed in nitrogen methyl pyrrolidone (NMP) at a mass ratio of 90:2.5:2.5:5 to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil and dried to prepare a sulfur positive electrode. At the same time, a lithium-sulfur battery was assembled using a polymer separator, a liquid electrolyte and metallic lithium as a negative electrode and its charge and discharge capacity was tested; wherein, the test conditions for the charge and discharge capacity were 0.5C charge-0.5C discharge (1C is 1670 mAh / g) at room temperature.
[0108] The test results are shown in Table 1:
[0109] Table 1
[0110]
[0111]
[0112] From Table 1 we can see that:
[0113] (1) The carbon sheet-carbon nanotube material obtained by the present invention can significantly improve the discharge specific capacity of lithium-sulfur batteries, and Figure 1It can be seen from the transmission electron microscope image in that the carbon nanotubes are evenly distributed on the carbon sheet; from Example 1 and Comparative Examples 1-2, it can be seen that compared with the carbon materials obtained in Comparative Examples 1 and 2, the carbon sheet-carbon nanotube material of the present invention has carbon nanotubes grown on the carbon sheet, has a multi-dimensional electron transmission path, and can significantly improve the battery discharge specific capacity; from Example 1 and Comparative Example 3, it can be seen that when preparing the carbon sheet, heating drying is used instead of freeze drying, which makes it difficult to form a thinner carbon sheet, and the specific surface area of the product decreases, thereby affecting the subsequent uniform generation of carbon nanotube materials, thereby affecting the performance of the lithium-sulfur battery.
[0114] (2) It can be seen from Examples 4-5 that the mass ratio of the template and the carbon source will affect the thickness and uniformity of the carbon sheet, affect the generation of carbon nanotubes, and further affect the performance of the battery; it can be seen from Examples 1 and 6-7 that when preparing the carbon sheet, if the annealing temperature is too high or too low, it will cause the chloride salt to melt and it will be difficult to maintain the carbon sheet morphology or the conductivity of the formed carbon sheet will decrease; it can be seen from Examples 1 and 8 that when the organic ligand is directly mixed with the carbon sheet, the metal salt and the solvent, the organic ligand and the metal salt will generate an organic framework material, which will make it impossible for the metal salt to be adsorbed on the carbon sheet, thereby affecting The growth of carbon nanotubes on the carbon sheet is affected; from Examples 9-10, even if dimethylimidazole is added later, if the stirring time is too long, it will affect the growth of carbon nanotubes, and if the stirring time is too short, it will affect the combination of dimethylimidazole and the metal salt on the carbon sheet; from Examples 1 and 11, it can be seen that replacing the freeze-drying in step (3) with heating drying will cause the metal particles adsorbed on the carbon sheet to agglomerate, affecting the distribution of carbon nanotubes; from Examples 1 and 12, it can be seen that the carbonized atmosphere will affect the growth of carbon nanotubes, thereby further affecting the performance of the lithium-sulfur battery.
[0115] In summary, the present invention provides a carbon sheet-carbon nanotube material and a preparation method and application thereof. The preparation method enables the obtained carbon sheet-carbon nanotube material to have a three-dimensional electronic conductive network, avoiding the problem of electron transmission being blocked due to the deposition of insulator sulfur, and the prepared carbon sheet-carbon nanotube material has a high specific surface area, and effectively improves the discharge specific capacity of the lithium-sulfur battery when used as a sulfur carrier.
[0116] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a carbon sheet-carbon nanotube material, characterized in that: The preparation method comprises the following steps: (1) mixing a template, a carbon source and a solvent and freeze-drying the mixture to obtain a powder; The mass ratio of the template to the carbon source in step (1) is (30-50):1; (2) annealing the powder in step (1) and then washing it to obtain a carbon sheet; The annealing temperature in step (2) is lower than the melting point of the template in step (1), and the annealing temperature in step (2) is 650-760° C.; (3) mixing a metal salt, an organic ligand, a solvent and the carbon sheet of step (2), and then performing solid-liquid separation and freeze-drying to obtain a mixture; The step (3) of mixing the metal salt, the organic ligand, the solvent and the carbon sheet of the step (2) comprises first mixing the metal salt, the solvent and the carbon sheet of the step (2), and then adding the organic ligand for mixing, wherein the time for adding the organic ligand for mixing is 0.5-5 minutes; (4) carbonizing the mixture of step (3) to obtain the carbon sheet-carbon nanotube material; The carbonization gas in step (4) includes an inert gas, or a mixture of a reducing gas and an inert gas.
2. The preparation method according to claim 1, characterized in that: The template in step (1) comprises chloride salt.
3. The preparation method according to claim 2, characterized in that: The template in step (1) is sodium chloride and / or potassium chloride.
4. The preparation method according to claim 1, characterized in that: The carbon source in step (1) includes any one of glucose, starch or sucrose, or a combination of at least two of them.
5. The preparation method according to claim 1, characterized in that: The solvent in step (1) includes deionized water.
6. The preparation method according to claim 1, characterized in that: The mixing time in step (1) is 20-40 minutes.
7. The preparation method according to claim 1, characterized in that: The annealing time in step (2) is 1-3h.
8. The preparation method according to claim 1, characterized in that: The cleaning solution used in step (2) includes deionized water and alcohol.
9. The preparation method according to claim 1, characterized in that: The number of cleanings in step (2) is 3-5 times.
10. The preparation method according to claim 1, characterized in that: The time for mixing the metal salt, the solvent and the carbon sheet in step (2) is 20-28 hours.
11. The preparation method according to claim 1, characterized in that: The metal salt in step (3) includes nitrate.
12. The preparation method according to claim 11, characterized in that: The nitrates include cobalt nitrate and nickel nitrate.
13. The preparation method according to claim 1, characterized in that: The organic ligand in step (3) includes dimethylimidazole.
14. The preparation method according to claim 1, characterized in that: The solvent in step (3) includes an alcohol solvent.
15. The preparation method according to claim 14, characterized in that: The solvent in step (3) is methanol.
16. The preparation method according to claim 1, characterized in that: The carbonization temperature in step (4) is 900-1000° C. and the time is 1-3 hours.
17. The preparation method according to claim 1, characterized in that: Step (4) further includes cooling and washing steps after the carbonization.
18. The preparation method according to claim 17, characterized in that: The washing comprises first washing the carbonized product 3-5 times with a mixed solution of deionized water and acid, and then washing it 3-5 times with a mixed solution of deionized water and alcohol.
19. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing the template, the carbon source and the solvent for 20-40 minutes, and then freeze-drying to obtain a powder; The mass ratio of the template to the carbon source is (30-50):1; (2) annealing the powder in step (1) at 650-760° C. for 1-3 h, and then washing with deionized water and alcohol for 3-5 times to obtain a carbon sheet; the annealing temperature is lower than the melting point of the template in step (1); (3) firstly mixing the metal salt, the solvent and the carbon sheet described in step (2) for 20-28 hours, then adding the organic ligand and mixing for 0.5-5 minutes, and then performing solid-liquid separation and freeze-drying to obtain a mixture; (4) Carbonizing the mixture of step (3) at a temperature of 900-1000° C. for 1-3 h in a mixed gas of reducing gas and inert gas, cooling, and then washing the carbonized product 3-5 times with a mixed solution of deionized water and acid, and then washing it 3-5 times with a mixed solution of deionized water and alcohol, to obtain the carbon sheet-carbon nanotube material.
20. A carbon sheet-carbon nanotube material, characterized in that: The carbon sheet-carbon nanotube material is prepared by the preparation method according to any one of claims 1 to 19.
21. A lithium-sulfur battery, characterized in that: The positive electrode material of the lithium-sulfur battery comprises sulfur and the carbon sheet-carbon nanotube material according to claim 20.
Citation Information
Patent Citations
Deposition matrix and preparation method thereof
CN107706354A
Tin elementary substance composite tungsten disulfide / reduced graphene oxide composite electrode material and preparation method and application thereof
CN111799458A